Community health workers at the dawn of a new era: 8. Incentives and remuneration - Christopher J. Colvin; Steve Hodgins; Henry B. Perry (BMC, 2021)
Abstract Background This is the eighth in our series of 11 papers on "CHWs at the Dawn of a New Era". Community health worker (CHW) incentives and remuneration are core issues that affect the performance of individual CHWs and the performance of the overall CHW programme. A better understanding of what motivates CHWs and a stronger awareness of the social justice dimensions of remuneration are essential in order to build stronger CHW programmes and to support the professionalization of the CHW workforce. Methods We provide examples of incentives that have been provided to CHWs and identify factors that motivate and demotivate CHWs. We developed our findings in this paper by synthesizing the findings of a recent review of CHW motivation and incentives in a wide variety of CHW programmes with detailed case study data about CHW compensation and incentives in 29 national CHW programmes. Results Incentives can be direct or indirect, and they can be complementary/demand-side incentives. Direct incentives can be financial or nonfinancial. Indirect incentives can be available through the health system or from the community, as can complementary, demand-side incentives. Motivation is sustained when CHWs feel they are a valued member of the health system and have a clear role and set of responsibilities within it. A sense of the "do-ability" of the CHW role is critical in maintaining CHW motivation. CHWs are best motivated by work that provides opportunities for personal growth and professional development, irrespective of the direct remuneration and technical skills obtained. Working and social relationships among CHWs themselves and between CHWs and other healthcare professionals and community members strongly shape CHW motivation. Conclusion Our findings support the recent guidelines for CHWs released by WHO in 2018 that call for CHWs to receive a financial package that corresponds to their job demands, complexity, number of hours worked, training, and the roles they undertake. The guidelines also call for written agreements that specify the CHW's role and responsibilities, working conditions, remuneration, and workers' rights.